Components of professional satisfaction among novice nurses - Bella Savitsky; Rachel Shvartsur; Yifat Findling; Anat Ereli; Tova Hendel (BMC, 2023)
Abstract Background In Israel there are only 6.53 nurses per 1000 citizens, compared to 8.8 nurses per 1000 citizens in the OECD countries. The nursing shortage is even more severe in peripheral areas, especially in southern Israel. Nurses` professional satisfaction is crucial for preserving the nursing workforce. This study aimed to assess job satisfaction among novice nurses and identify components of professional satisfaction. Methods Cross-sectional study of 216 novice nurses who graduated in 2018-2022 and were approached ten months after graduation. Job satisfaction components were constructed using factor analysis. Results Professional satisfaction was based mainly on the intrinsic characteristics of the occupation related to personal accomplishment and organizational culture. In a multivariable model, a one-point increase in mean satisfaction with the training period during studies in the nursing department was associated with a more than a three-fold elevation in the odds for high and very high professional satisfaction (OR 3.0, 95% CI 1.7-5.1). Odds for high and very high professional satisfaction were more than four-fold and two-fold higher among graduates who rated their level of control over work schedule as high and medium vs. low (OR 4.2, 95% CI 1.0-16.7 and OR 2.8, 95% CI 1.2-6.3, respectively). Work-life balance without disturbance to daily life by work was found significantly associated with higher odds for high and very high satisfaction. Nurses who plan to continue professional development, i.e., an advanced professional course or Master's degree, had significantly higher mean professional satisfaction scales than others (4.2 vs. 3.7, p = .009 and 4.2 vs. 3.9, p < .001, respectively). Conclusion The most important components of professional satisfaction among novice nurses are self-accomplishment, which was built from work-related challenges, interest and variety of tasks, personal growth and development, and the possibility of contributing to patients` care and organizational culture, which was built from relationships with co-workers. Persons who manage nurses should cultivate an atmosphere of support and guidance, provide new nurses with interesting work tasks, and increase their ability to control their work schedule. Young nurses should be encouraged to continue their professional and academic education.